Exposição ocupacional às radiações ionizantes durante cirurgias ortopédicas guiadas fluoroscopicamente - Santos, Romilda Prado dos (2012)
Radiology has been considered one of the areas of medicine that most devel-ops, especially with the contribution of new technologies. Among the applications of Interventional Radiology highlights the use of fluoroscopy in the surgical center in addition to co-orthopedic surgeries, the object of the present research. Entretan-to some complex and lengthy fluoroscopically guided procedures can result in high levels of occupational exposure to ionizing radiation for e-quipe orthopedic surgery and health workers, induce serious damage to health. Considering these aspects, the general objective of this research is to de-termine the occupational exposure of the team of orthopedic surgery proce-dures guided by fluoroscopy and verify observed among the surgeries that offer greater occupational exposure to ionizing radiation, but also the application of basic principles of radiological protection in these procedures. The methodology for this research was the qualitative and quantitative exploratory type. The research was conducted at Hospital de Clinicas, Federal University of Curitiba (UFPR). Study subjects were members of the team of orthopedic surgery, or orthopedic doctors, residents, anesthesia, surgical instrumentator, technicians and nursing assistants, and nurses. Data collection was performed from January 1 to May 30, 2011. Contributors to the survey, 44 workers who answered a news conference, and a questionnaire with 25 closed questions of. was divided in four groups of eleven participants each, followed by document analysis and monitoring of the area and searched individually. The results we-strated that the health sector professionals surveyed were exposed to ionizing radiation, due to demand-driven surgery equipment emitting ionizing radiation fluoroscopically, and the lack of knowledge in radioprote-tion. Before these findings were suggested by the groups pre-vention measures of these exposures to minimize possible biological effects of ionizing radiation-tions. It was concluded that occupational exposure exists with re-worked in the sector researched, they have little knowledge about the use of radiation protection equipment in surgical procedures with equipment emitting ionizing radiation, properly use the monitors indi-tions.